2022
DOI: 10.3390/jcm11143978
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Systemic Immune-Inflammation Index among Critically Ill Patients with Acute Kidney Injury: A Retrospective Cohort Study

Abstract: Inflammation plays a significant role in the occurrence and development of acute kidney injury (AKI). Evidence regarding the prognostic effect of the systemic immune-inflammation index (SII) in critically ill patients with AKI is scarce. The aim of this study was to assess the association between SII and all-cause mortality in these patients. Detailed clinical data were extracted from the Medical Information Mart for Intensive Care Database (MIMIC)-IV. The primary outcome was set as the in-hospital mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The relationship between SII levels and prognosis in other populations has also been controversial in previous studies. Jia L et al found a similar J-shaped relationship in patients with acute kidney injury [12]. However, a recent study found a linear positive association in patients with acute ischemic stroke [37].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The relationship between SII levels and prognosis in other populations has also been controversial in previous studies. Jia L et al found a similar J-shaped relationship in patients with acute kidney injury [12]. However, a recent study found a linear positive association in patients with acute ischemic stroke [37].…”
Section: Discussionmentioning
confidence: 86%
“…The systemic immune-inflammation index (SII) is a novel parameter based on lymphocyte, neutrophil, and platelet counts, which has the benefit of economics and convenience and can simultaneously reflect patients' inflammatory and immune status [9]. The role of SII in predicting the survival of patients with cardiovascular disease [10], malignancy [11], and acute kidney injury [12] has been reported. We hypothesized that SII is associated with the prognosis of critically ill patients with sepsis and may be a potential early screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the potential value of the NLR, PLR, and PWR in predicting POD after lower limb, head and neck free-flap reconstruction, total hip arthroplasty, abdominal surgery, oesophagectomy carotid endarterectomy, and cardiac surgery [11][12][13][14][15]. As a white-cell derived inflammatory biomarker, systemic immune inflammation index (SII) has been used to predict ischemic stroke, delayed vasospasm, microvascular dysfunction, and acute kidney injury [16][17][18][19]. However, the SII has not been applied to predict POD in elderly patients after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Xie et al [ 41 ] discovered a favorable correlation between SII and abdominal aortic calcification, a frequent CKD consequence. In a cohort investigation of critically ill AKI patients, Lan et al [ 42 ] discovered a J-shaped relationship between SII and all-cause death in these patients.…”
Section: Discussionmentioning
confidence: 99%